Hubungan antara Parental Resilience dengan Quality of Life pada Ibu yang Memiliki Anak Cerebral Palsy - Zuhro Nazifah Chair; Zaujatul Amna (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Cerebral palsy (CP) is a permanent condition affecting motor control due to brain lesions, making affected children highly dependent on their mothers as primary caregivers. This situation frequently triggers psychological disturbances — including stress, depression, and physical fatigue — that directly diminish maternal quality of life (QoL). Parental resilience is conceptualised as the adaptive capacity mothers need to sustain long-term caregiving. This study examined the relationship between parental resilience and quality of life among mothers of children with CP in Aceh Besar District, Indonesia. A correlational quantitative design was employed with 60 mothers selected through quota sampling with strict inclusion criteria. The Parental Resilience Elements Questionnaire (PERQ) and the Quality of Life Autism (QoLA) – Parent Version were used as instruments. Non-parametric Spearman Rho analysis yielded a correlation coefficient of rs = 0.505 (p < 0.001), indicating a moderate positive relationship. The squared correlation coefficient (rs² = 0.255) suggests parental resilience accounts for approximately 25.5% of QoL variance. The modest contribution is discussed in terms of cultural fit of the instrument and the role of other variables such as social support, spirituality, and hardiness. Findings underscore the importance of culturally sensitive resilience programmes for mothers of children with CP.